Erratum: High speed sCMOS‐based oblique plane microscopy applied to the study of calcium dynamics in cardiac myocytes: [J. Biophotonics 9, No. 3, 311–323 (2016)]. Issue 5 (3rd May 2017) - Sikkel, Markus B.; Kumar, Sunil; Maioli, Vincent; Rowlands, Christina; Gordon, Fabiana; Harding, Sian E.; Lyon, Alexander R.; MacLeod, Kenneth T.; Dunsby, Chris
Abstract: In the article by M.B. Sikkel et al. (doi: 10.1002/jbio.201500193), published in J. Biophotonics9, 311–323 (2016), an error occurred in the computer code that was used to generate Figure 3. This erratum is published to correct Figure 3, the calculated value of t geom and the experimentally determined value of t optics in the text of the article. Abstract :